2022
DOI: 10.3390/jpm12030399
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxyphenyllactic Acid in Cerebrospinal Fluid as a Possible Marker of Post-Neurosurgical Meningitis: Retrospective Study

Abstract: The search for new potential biomarkers for the diagnostics of post-neurosurgical bacterial meningitis is required because of the difficulties in its early verification using results of the routine laboratory and biochemical analyses of the cerebrospinal fluid (CSF). The goal of the study was to determine the contents of the aromatic metabolites and biomarkers in the CSF samples of the post-neurosurgical patients (n = 82) and their potential diagnostical significance for the evaluation of the risk of post-neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Experimental studies demonstrated their pathophysiological role in sepsis development [ 11 ]. Clinical studies revealed their diagnostic significance in sepsis and septic shock caused by various pathologies [ 12 , 13 ], such as community-acquired pneumonia [ 14 ], acute surgical diseases of the abdominal organs [ 15 ], acute or chronic (end stage) renal failure [ 16 ], postoperative cardiosurgical complications [ 17 ], and post-neurosurgical meningitis [ 18 ]. There are positive correlations between the sepsis-associated aromatic metabolites phenyllactic, p -hydroxyphenylacetic, and p -hydroxyphenyllactic ( p -HPhLA) acids and the clinical scales (SOFA and APACHE II), serum lactate, and procalcitonin [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies demonstrated their pathophysiological role in sepsis development [ 11 ]. Clinical studies revealed their diagnostic significance in sepsis and septic shock caused by various pathologies [ 12 , 13 ], such as community-acquired pneumonia [ 14 ], acute surgical diseases of the abdominal organs [ 15 ], acute or chronic (end stage) renal failure [ 16 ], postoperative cardiosurgical complications [ 17 ], and post-neurosurgical meningitis [ 18 ]. There are positive correlations between the sepsis-associated aromatic metabolites phenyllactic, p -hydroxyphenylacetic, and p -hydroxyphenyllactic ( p -HPhLA) acids and the clinical scales (SOFA and APACHE II), serum lactate, and procalcitonin [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the practical use of the aromatic metabolites as a diagnostic tool, it is important to find out if one or a number of them demonstrates any predictive value for the outcome of critically ill patients. Previous clinical studies have described the univariate predictive models based on concentrations of one or a sum of several metabolites (phenyllactic, p -hydroxyphenylacetic acids, and p -HPhLA) [ 13 , 15 , 18 ]. In addition, it is important to reveal if these compounds could be used as predictive markers on the day of admission to the intensive care unit (ICU), by analogy with the APACHE II scale, thus, indicating patients with more severe disease and a higher risk of death.…”
Section: Introductionmentioning
confidence: 99%